A New Honorific Inscription for Sabina from Lyttos - Tsolakis, Georgios (Tekmeria, 2025)
The present article publishes a new honorific inscription for Sabina, wife of Hadrian, from the Cretan city of Lyttos. The text of the fragmentary statue base, inscribed in the years just before or during the 120s A.D. and found in the Sebasteion during the 2024 season of the Lyktos Archaeological Project, is only partially preserved. Nevertheless, it reveals unusual features in Lyttian honorific practice, including the sequence of Hadrian's titles and the use of ἐπί with genitive / dative, and adds to the small corpus of Cretan inscriptions for Sabina. The article further contributes to the discussion of Sabina's acquisition of the title Augusta and to the practice of the imperial cult in Lyttos.